2013
DOI: 10.1248/bpb.b12-01102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Drug Delivery Systems in Cancer Chemotherapy: Review of the Efficacy and Side Effects of Approved Drugs

Abstract: In recent years, drug delivery systems (DDS) have been developed, along with anticancer agents for those systems based on the concept of achieving a better clinical response and tolerability. Several clinical trials have shown that these drugs have better clinical effects in the treatment of many cancers, leading to their expanded indications. Liposomal doxorubicin is one DDS agent used to treat AIDS-related Kaposi's sarcoma and ovarian cancer in Japan. In addition to those two indications, the Food and Drug A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(134 citation statements)
references
References 9 publications
(7 reference statements)
0
128
0
1
Order By: Relevance
“…Mice bearing tumors between 10 mm 3 fluorescently labeled alginate strands conjugated to complementary ODNs were administered i.v. Imaging of mice first revealed that i.v.-administered alginate strands collected in the tumors of all mice at 24 h postadministration, presumably through the EPR effect ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mice bearing tumors between 10 mm 3 fluorescently labeled alginate strands conjugated to complementary ODNs were administered i.v. Imaging of mice first revealed that i.v.-administered alginate strands collected in the tumors of all mice at 24 h postadministration, presumably through the EPR effect ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Encapsulation drugs in liposomal nanoparticles show promising results in the clinical setting. Doxorubicin HCl liposomal injection (Doxil) was approved for the treatment of AIDS-related Kaposi's sarcoma (USA in 1995 and Japan in 2007), and for the treatment of ovarian cancer (USA in 1999 and Japan in 2009) after failure of prior systemic chemotherapy or intolerance or after failure of platinumbased chemotherapy [125] . In addition, in 2007 the FDA approved Doxil for the treatment of multiple myeloma in combination with bortezomib.…”
Section: Evading P-gp (Nanoparticle Drug Delivery Systems)mentioning
confidence: 99%
“…24 Magnetic nanoparticle (MNP) drug delivery promises to be highly synergistic with MRgFUS. MNPs can be conjugated to chemotherapy and enriched in a targeted area by using a magnetic field generated by an external magnet to attract them, which is termed magnetic targeting (MT).…”
Section: Nanoparticle Conjugation and Mrgfusmentioning
confidence: 99%